Predictors of asthma following severe respiratory syncytial virus (RSV) bronchiolitis in early childhood. Issue 12 (6th May 2016) - Lu, Susan; Hartert, Tina V.; Everard, Mark L.; Giezek, Hilde; Nelsen, Linda; Mehta, Anish; Patel, Hima; Knorr, Barbara; Reiss, Theodore F.
Summary: Background: We sought to identify predictors of asthma development following severe early childhood RSV bronchiolitis. Different definitions of asthma were also compared. Methods: This longitudinal, observational study (N = 343) followed patients (<2 years old) from a placebo‐controlled trial (N = 979) of montelukast after RSV bronchiolitis to identify clinical, demographic, or biochemical predictors of asthma, atopic disorders, and chronic asthma therapy use at 6 years of age (Clinical Trials Registry Number: NCT01140048). Asthma (primary definition) was based on parental identification of wheeze at 6 AND 12 months before 6 years of age; definitions based on physician diagnosis as well as parental identification of wheeze at 6 OR 12 months (to consider seasonal effect) were also assessed. Post‐hoc analyses evaluated agreement among asthma diagnosis criteria. Results: Prevalence of asthma (primary definition by parental identification), asthma (physician diagnosis), atopic disorders, and chronic asthma therapy use (parental identification) was 6.1%, 22.4%, 36.2%, and 14.5%, respectively. Predictors for asthma (primary definition) included male gender, a relative with asthma, and RAST positive for dog dander; for physician diagnosis of asthma, high severity score for RSV bronchiolitis, high respiratory rate, and asthma diagnosis before enrollment. Predictors of atopic disorders included allergic rhinitis before enrollment, a relative with asthma, and the plasma biomarkers IL‐5, IL‐16, and IL‐18. Predictors of chronic asthma therapy use included asthma diagnosis before enrollment and geographic region (Europe and Africa). Only 42% of patients with asthma (primary definition) also met the asthma definition by physician diagnosis and chronic asthma therapy use. Conclusion: Among children with early RSV bronchiolitis, hereditary factors (i.e., having a relative with asthma) and RSV bronchiolitis severity were predictors of asthma and atopic disorders at 6 years of age. Of interest, there was poor agreement among the asthma definitions evaluated.Pediatr Pulmonol. 2016;51:1382–1392. © 2016 Wiley Periodicals, Inc.